The effects of weight self-stigma on psychological distress in adolescents: the chain-mediated roles of fear of negative appearance evaluation and social appearance anxiety - Tang, Changhao; Zhang, Xinmiao; Zhou, Chuncen; Li, Kai; Cai, Yujun (Frontiers in Psychology, 2025)
PurposeThis study aimed to investigate the effects of weight self-stigma on psychological distress in adolescents and to examine the chain-mediating roles of fear of negative appearance evaluation and social appearance anxiety.Patients and methodsA multistage sampling method was used to conduct a questionnaire survey of 2,076 adolescents in Changsha, Zhuzhou, and Yueyang in Hunan Province. The Weight Self-Stigma Questionnaire, the Fear of Negative Appearance Evaluation Scale, the Social Appearance Anxiety Scale, and the Depression, Anxiety, and Stress Scale-21 were used in the investigation. The collected data underwent descriptive statistical analyses, correlation analyses, and chain mediation model tests.ResultsA significant positive correlation was observed between adolescent weight self-stigma and fear of negative appearance evaluation, social appearance anxiety, and psychological distress (p < 0.01). Weight self-stigma was found to affect psychological distress in adolescents (effect value = 0.087) directly and also exert an indirect effect through the mediating roles of fear of negative appearance evaluation (effect size = 0.062) and social appearance anxiety (effect size = 0.061), as well as the chain mediating effect of these two indirectly affects psychological distress (effect size = 0.137).ConclusionWeight self-stigma has a direct and positive impact on adolescent psychological distress. Fear of negative appearance evaluation and social appearance anxiety serve as mediators in this relationship. Meanwhile, fear of negative appearance evaluation and social appearance anxiety could also chain-mediate the relationship between adolescent weight self-stigma and psychological distress. It is necessary to develop effective intervention strategies to enhance physical activity and dietary management, thereby reducing weight self-stigma and promoting healthy physical and mental development in adolescents.